Modèles de représentation sur la parentalité sociale du point de vue des jeunes portugais - Mocetão, Cristina (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2016)
Growing up in a stepfamily has become an increasingly common experience in dealing with the evolution of modern families. The aim of this research was to understand the views of young people about stepfamily. For this, the author administered a questionnaire to 477 teenager (14 and 18 years old) living in a family configuration diversity. The main findings indicate have no significant differences in the performances of the stepfather and stepmother. However, they are described as “another different”. But, when associated with parental roles and coexistence mode, the stepfather and stepmother are qualified as closest members.